2009
DOI: 10.1002/jmv.21677
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 reverse transcriptase drug‐resistance mutations in chronically infected individuals receiving or naïve to HAART in Cameroon

Abstract: The most common first-line, highly active anti-retroviral therapy (HAART) received by individuals infected with HIV-1 in Cameroon is the combination therapy Triomune, comprised of two nucleoside reverse transcriptase inhibitors (NRTI) and one non-NRTI (NNRTI). To examine the efficacy of these drugs in Cameroon, where diverse non-B HIV-1 subtypes and recombinant viruses predominate, the reverse transcriptase (RT) viral sequences in patient plasma were analyzed for the presence of mutations that confer drug resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
2
17
1
Order By: Relevance
“…Of the articles and abstracts searched, seven fulfilled the criteria for the analysis of acquired HIV drug resistance [26–33] and twenty-two for the analysis of transmitted HIV drug resistance [24, 25, 26, 28, 3451] (Figure 1). Two papers provided data for both analyses [28, 30].…”
Section: Resultsmentioning
confidence: 99%
“…Of the articles and abstracts searched, seven fulfilled the criteria for the analysis of acquired HIV drug resistance [26–33] and twenty-two for the analysis of transmitted HIV drug resistance [24, 25, 26, 28, 3451] (Figure 1). Two papers provided data for both analyses [28, 30].…”
Section: Resultsmentioning
confidence: 99%
“…Previous data concerning the prevalence of drug resistance among ART‐experienced Cameroonian patients have been contradictory. In 2009 and 2010 two studies reported a drug resistance prevalence of 39 and 46% to NRTI and NNRTI, respectively [Kouanfack et al, 2009; Burda et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
“…Transmitted resistance mutations affecting NRTIs, NNRTIs, and to a lesser extent PIs have been reported in patients with CRF_AG [910], similar to patients with other HIV subtypes and recombinant forms. Although many of our patient’s pre-treatment protease mutations are highly prevalent in treatment-naïve CRF_AG patients, 2–3 are major protease mutations [11–12] prevalent in less than 0.5% of treatment-naïve CRF_AG patients [7] (Table 1).…”
Section: Discussionmentioning
confidence: 99%